Constructive journalism : precedents, principles, and practices - Bro, Peter (London : Routledge, Taylor & Francis Group, 2024)
"This book offers a deep and comprehensive overview of constructive journalism, setting out the guiding principles and practices for a journalism that aims to do more than simply inform about problems. In this authoritative yet concise volume, Peter Bro asks what does constructive journalism mean, what are the underlying principles, how is it practiced and in what ways does it differ from other types of journalism? Drawing on studies of the rapidly growing number of works by both journalism practitioners and researchers, the book reaches beyond these questions to show how the notion of being constructive has been a part of journalism from the very beginning of the profession. This introduction to what constructive journalism is, was and what it can accomplish will guide new journalists, journalism, media and mass communication students, and scholars working on journalistic theory and practice"--
Introduction of constructive journalism -- Precedents of constructive journalism -- Principles of constructive journalism -- Practices of constructive journalism.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Journalism